Analisis Perbandingan Risk dan Return Saham Syariah dengan Saham Konvensional (Studi Empiris pada Jakarta Islamic Index (JII) dan LQ45 Periode 2017-2022) - Alfarisi, Muhammad Ayyub; Badina, Tenny; Ainun Najib, Mohamad (Universitas Muhammadiyah Surabaya, 2024)
This study was prepared to determine the difference in average return and risk of Islamic stocks in the Jakarta Islamic Index (JII) and conventional stocks in LQ45 in the period 2017 to 2022. This study also analyzes the variables of exchange rates, inflation, the fed interest rate, and covid-19 in influencing stock returns on companies in the Jakarta Islamic Index and LQ45. This type of research is descriptive research with a quantitative approach. The research location is the Indonesia Stock Exchange website www.idx.co.id as a secondary data provider in the form of names of issuers included in the JII and LQ45 indices and quarterly stock closing price data for the period 2017 to 2022. The results of descriptive analysis show that the risk of Islamic stocks is higher than conventional stocks (0.1885> 0.1723 or 8.85%> 7.23%). The return rate is higher for Islamic stocks than conventional stocks (0.0196> 0.0018 or 1.96%> 0.18%). Based on the results of different tests using the Independent Sample t-test and Man-Whitney, it was found that there was no significant difference between the Return and Risk of Islamic stocks and conventional stocks. The results of macroeconomic influence research show that the fed interest rate and covid-19 have a positive and significant effect on stock returns. While exchange rates and inflation have a negative effect on stock returns. Keyword: Conventional Shares, Covid-19, Exchange Rate, Inflation, Interest Rates, Return, Risk, Sharia Shares